Respostas ecofisiológicas de sementes e mudas de jabuticabeira-açu tratadas com terra de diatomácea ou prolina e submetidas a níveis de estresse salino - Alamino, Douglas Alvarez (2021)
Changes in soil exploitation patterns, rainfall regimes and use of low low-quality irrigation water have been responsible for the increase in areas subject to salinization processes. Understanding how native species respond to such pressures has become increasingly important. Thus, the present study aimed t o evaluate the ecophysiological responses of seeds and seedlings of jabuticabeira (Plinia cauliflora. DC.) Kausel, treated with diatomaceous earth or proline and subjected to saline stress levels. For that, the tests were carried out in two stages, where, in the first, it was evaluated, through germination tests, from seeds extracted from ripe fruits, in a controlled environment, the resumption of the metabolic processes of seeds treated with diatomaceous earth (0 ; 1.0; 2.0; 3.0; 4.0; 5.0 g L L-1) or proline (0; 0.1; 0.2; 0.3; 0.4; 0.5 g L L-1) and subjected to salinity levels (0; 2.0; 4.0; 6.0; 8.0 and 10.0 dS m m-1). The establishment and development of seedlings from germination were also evaluated. The second stage consisted of monitoring the development, wat er consumption, visual diagnosis and leaf nutrient content, morphoanatomy of vegetative structures and survival of bacterial microbiota. For that, seedlings were conducted in two cultivation systems, the first with drainage lysimeters, built by 5 5-liter buc kets, filled with soil, coupled to water collection containers at the base of each system. The second system was the capillary hydroponic system, built using PET bottles, using vermiculite as a substrate and cotton mesh as a carrier agent for the solutions . In both cases, the same treatment and salinity levels described in the germination process were used. The isolation and morphological description of the bacteria present in the soil and in the leaching water of the lysimetry process were also carried out at the end of the tests (at 90 days). From the data collected, it was possible to verify a reduction in the percentage of germination, IVG, VMG and an increase in TMG, both in seeds with treatment and control . The seedlings showed no morphological changes . In seedlings, the increase in salinity levels negatively affected all evaluated parameters, reducing crown and total height, stem and neck diameter, number of new shoots and leaves, root length and density, salinity tolerance index and quality of seedlin gs. Dickson, fresh and dry mass of stem, leaves, roots and total, in addition to nutritional and morphoanatomical aspects. The diatomaceous earth or proline treatment provided a slight improvement in the growth variables, with better results being found wi th the use of 3.0 and 0.3 g kg of substrate substrate-1, respectively. The bacterial microbiota remained unchanged. It was concluded that the increase in salinity generates negative effects and that the diatomaceous earth treatment was more efficient in minimizing t he effects of saline stress than proline in jabuticabeira seedlings.